Work and Mental Health in Social Context - Tausig, Mark.; Fenwick, Rudy.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2012)
The authors of Work and Mental Health in Social Context take a different approach to understanding the causes of job stress. Job stress is systematically created by the characteristics of the jobs themselves: by the workers$1 (Boccupation, the organizations in which they work, their placements in different labor markets, and by broader social, economic and institutional structures, processes and events. And disparities in job stress are systematically determined in much the same way as are other disparities in health, income, and mobility opportunities. In taking this approach, the authors draw on the observations and insights from a diverse field of sociological and economic theories and research. These go back to the nineteenth century writings of Marx, Weber and Durkheim on the relationship between work and well-being. They also include the more contemporary work in organizational sociology, structural labor market research from sociology and economics, research on unemployment and economic cycles, and research on institutional environments. This has allowed the authors to develop a unified framework that extends sociological models of income inequality and (3z(Bstatus(3y (Battainment (or allocation) to the explanation of non-economic, health-related outcomes of work.s
Preface.-Introduction: Job Stress and Where it Comes From.-Chapter 2. Job Structures, Job Stress and Mental Health.-Chapter 3. Organizational Determinants of Job Stressors -- Chapter 4. Occupational Determinants of Job Stress: Socioeconomic Status and Segmented Labor Markets.-Chapter 5. Macroeconomic Change, Unemployment and Job Stress -- Chapter 6. Institutional Factors.-Chapter 7. Work and Mental Health in Social Context.
Keywords: Social sciences; Medicine; Social policy; Social Sciences; Sociology, general; Medicine/Public Health, general; Social Policy